Perceived Stigma and Barriers to Accessing Services: Experience of Caregivers of Autistic Children Residing in Latin America. (January 2022) - Montenegro, María Cecilia; Abdul-Chani, Monica; Valdez, Daniel; Rosoli, Analia; Garrido, Gabriela; Cukier, Sebastian; Paula, Cristiane Silvestre; Garcia, Ricardo; Rattazzi, Alexia; Montiel-Nava, Cecilia
Highlights: Experience of ASD in families is heavily influenced by environmental factors such as country of residence. Caregivers of female children reported almost 8% higher agreement to have experienced perceived stigma Caregivers of adult children with ASD reported feeling helpless for having an autistic child more frequently than other age groups Abstract: Background: Relationship of perceived stigma and barrier to service access among Latino populations with autism in cross-cultural settings has not been fully explored. Aim: The present study explored the relationship between difficulty accessing services and perceived stigma among caregivers of autistic children in Latin America. Additionally, explore contextual factors that better explain the perception of stigma when accessing services. Methods and Procedure: Approximately 2500 caregivers from six Latin American countries completed an online survey. Descriptive inferential analysis and a pointbiserial correlation were conducted to understand direct relationship between difficulty accessing services and perceived stigma and to test their relationship. Added contextual factors contributing to this relationship were examined through a binary logistic regression. Outcomes and Results: Barriers to accessing services predicted stigma. Contextual factors such as country of residence, frustration experienced by caregivers, gender of autistic child and challenging behaviours had higher odds of experiencing some form of perceived stigma. Conclusions and Implications: These results suggest experiences with stigma to be heavily influenced by environmental factors such cultural differences which in combination with contextual factors could further increase the likelihood of perceiving stigma. When observing stigma within a social–cognitive approach, it is possible that a strong-held adherence to cultural norms, in addition to negative experiences (e.g., frustration) when accessing services, could be influencing caregivers perceived stigma.